A study of clinical and functional outcome of primary total knee arthroplasty using posterior cruciate substitute design - A. M., Radhakrishna; S., Shivananda; S., Girish (International Journal of Research in Orthopaedics, 2017)
Background: To study the clinical and functional outcome in a consecutive series of Total Knee Arthroplasty using Posterior cruciate substituting (PS) design using the Knee Society Score(KSS). The objectives of the study was 1) To assess the improvement in pain relief post-operatively, stability, mobility of the joint and to assess the correction of deformities. 2) To compare the knee clinical score (KCS) pre-operatively and post-operatively. 3) To compare the knee functional score (KFS) pre-operatively and post-operatively. 4) To assess the radiological outcome of total knee arthroplasty. 5) To study the association between the KCS and the KFS. Methods: The study was conducted on patients who have undergone Primary total knee replacement, in Department of Orthopaedics, KIMS hospital from June 2014 to February 2017. The patient was assessed clinically, functionally using the Knee Society Score and a radiographic evaluation was done. These evaluations were performed at 6weeks, 12 weeks, 24 weeks and 1year follow up visits. Results: At 1 year follow up of 60 knees, the average pre-op knee clinical score and functional score of 24.7 and 41.2 improved to an average post-op score of 89.9 and 87.8 respectively. Knee clinical and functional score grade of excellent to good was seen in 96.7% (58 knees of 60). Significant association was seen between KCS and KFS. 5 patients had delayed wound healing and one patient had deep infection. Alignment of prosthesis was found satisfactory in all patients. Flexion deformity, valgus and varus correction achieved in all the patients. Conclusions: Total knee arthroplasty using posterior cruciate substituting designs resulted in excellent relief of pain, range of motion, restoration of function, low prevalence of patellofemoral complications and continues to function well during the follow-up period. Improvement in clinical score correlated significantly with improvement in functional score. Knee society scoring system effective in evaluating clinical, functional and radiological outcomes.